“The boy could not distinguish faces”: the world through the eyes of a child in F. Gorenstein’s story The House with a Turret - Lekmanov, Oleg (Literatūra, 2023)
The article about Friedrich Gorenstein’s story The House with a Turret deals with the difference between the points of view of the protagonist of the story and the author’s point of view on the world surrounding the protagonist. From the beginning to the end of the story, the boy, the main character of the story, learns to distinguish good from evil and good people from bad.
Keywords: Friedrich Gorenstein; the theme of childhood in literature; trauma